How Purchase Decision Mediates Electronic Word of Mouth's Impact on Customer Satisfaction: A Case in Shopee Application - Heda, Bonita Septiani; Yulianto, Edy; Sunarti, Sunarti (Profit: Jurnal Adminsitrasi Bisnis, 2024)
Examination of the relationships between Electronic Word of Mouth (eWOM), Purchase Decision (PDC), and Customer Satisfaction (CSF) within the context of Shopee, an Indonesian top-commerce platform. The study aims to analyze the influence of eWOM on PDC, the impact of PDC on CSF, and the mediating role of PDC in the relationship between eWOM and CSF. The research employs nonprobability-purposive sampling to collect data from 182 Shopee users in Indonesia exposed to eWOM and actively making PDC. The five Likert-scale questionnaires were distributed online for measurement. Partial Least Squares (PLS) analysis confirms significant positive relationships between eWOM toward PDC, PDC toward CSF, and eWOM toward CSF. Notably, PDC emerges as a crucial mediator, bridging the relationship between eWOM and CSF. The results highlight the significance of eWOM in influencing PDC and perceptions of e-commerce customers. The recommendation is that marketers and online sellers can foster positive eWOM through clear, detailed, and favourable reviews. They are enhancing PDC by streamlining the purchasing process and ensuring satisfactory experiences. For future research, exploring the moderating effects of demographic variables and investigating the impact of website design and social influence on eWOM, PDC, and CSF could enrich understanding in this domain.